Quantification of serotonin O-sulphate by LC-MS method in plasma of healthy volunteers - Lozda, Raimonds; Purviņš, Indulis (Frontiers in Pharmacology, 2014)
The objective of this study was to test the hypothesis that serotonin O-sulphate (5 -HT-SO4) could be quantified in human plasma using modern liquid chromatography–mass spectrometry (LC-MS) method as well as develop and validate that method. First, a suitable LC-MS method for detection of 5-HT-SO4 in human plasma samples was developed and validated. Second, a Pilot phase involving four healthy volunteers was executed, where a basal plasma level of 5-HT-SO4 was measured for all subjects and for one after the intake of 100 mg of a 5-hydroxytryptophan (5-HTP) -containing food supplement used to promote serotonergic stimulation of the central nervous system. The basal level of 0.9 – 2.8 ng/mL of 5-HT-SO4 was observed. The changes of plasma 5HT-O-SO4 showed 1.2 ng/mL before and 22.6 ng/mL 1 h after stimulation. Finally, nine healthy volunteers were selected for the Study phase, where a basal plasma level of 5-HT-SO4 was measured before and after the intake of 5-HTP. One hour after stimulation, six study subjects showed a decrease in 5-HT-SO4 levels while three subjects showed an increase. The changes of plasma 5HT-O-SO4 from the Study phase showed an average 5-HT-SO4 level of 19.2 ng/mL before and 15.7 ng/mL 1 h after stimulation indicating ability of method to emphasise quantitative changes. This was the first study in which naturally occurring 5-HT-SO4 was detected in the samples of human plasma obtained from healthy volunteers. The method developed herein is specific to the measurement of 5-HT-SO4, sensitive enough to quantify intra-individual changes in the samples of plasma and opens up new possibilities to evaluate pathways of serotonin metabolism by minimally invasive methods. The discovery of novel biomarkers using such approaches is increasingly required to expedite development of mechanism-based therapeutics and patient stratification.